2016
DOI: 10.12659/msm.899004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intellectual, Physical, and Social Activity on Further Prognosis in Mild Cognitive Impairment

Abstract: BackgroundOur goal was to specify the relationship between the level of activity (intellectual, physical, and social) in persons diagnosed with mild cognitive impairment (MCI) and the further progression of cognitive dysfunction.Material/MethodsWe examined 193 patients diagnosed with MCI (according to the criteria of the Working Group on Mild Cognitive Impairment) and under treatment at our Mental Disorders Clinic. It was assumed that these persons would remain under systematic psychiatric observation until de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
(37 reference statements)
3
20
0
Order By: Relevance
“…This is in accord with a recent longitudinal study which showed that late-life leisure activities protect against cognitive impairment among elderly Chinese, while the protective effect is more profound for educated elderly [185]. Another study found significant differences in the level of social activity at baseline between those with stable MCI and those who had progressed to dementia, indicating that social activity affects the further prognosis in MCI in a positive way [186]. However, two other studies did not find a significant protective effect of late-life social support activities [187] or of midlife social engagement [188] on the risk of dementia.…”
Section: Leisure Activity and Cognitive Reservesupporting
confidence: 87%
“…This is in accord with a recent longitudinal study which showed that late-life leisure activities protect against cognitive impairment among elderly Chinese, while the protective effect is more profound for educated elderly [185]. Another study found significant differences in the level of social activity at baseline between those with stable MCI and those who had progressed to dementia, indicating that social activity affects the further prognosis in MCI in a positive way [186]. However, two other studies did not find a significant protective effect of late-life social support activities [187] or of midlife social engagement [188] on the risk of dementia.…”
Section: Leisure Activity and Cognitive Reservesupporting
confidence: 87%
“…It has been reported that higher levels of instrumental ADL are associated with higher global cognition in the populations among healthy people as well as patients with MCI and dementia . In addition, several studies have demonstrated that IADL impairment contributes to predicting onset of dementia in the older people . The present study extends these findings to the healthy individuals who are much older in the context of the oldest‐old without cognitive impairment.…”
Section: Discussionsupporting
confidence: 66%
“…[31][32][33][34] Previous studies have indicated that activities of daily living (ADL) and instrumental activities of daily living (IADL) are closely related to cognitive impairment. 7,35 Interestingly, some researchers have argued that hand grip strength is a preventive factor of cognitive decline. [36][37][38] The similarities in the brain areas and networks involved in cognition and muscle strength (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…4,40 Other studies have identified cognitive impairment's association with socioeconomic status, religion, and gender. 33,35 The focus of the present study is the association between social club and cognitive function. Crosssectional and longitudinal studies have verified the association between social club and cognitive function.…”
Section: Introductionmentioning
confidence: 99%